Retirement Home? Ageing Migrant Workers in France and the Question of Return - Hunter, Alistair (IMISCOE Research Series,, 2018)
This open access book offers new insights into the ageing-migration nexus and the nature of home. Documenting the hidden world of France's migrant worker hostels, it explores why older North and West African men continue to live past retirement age in this sub-standard housing. Conventional wisdom holds that at retirement labour migrants ought to instead return to their families in home countries, where their French pensions would have far greater purchasing power. This paradox is the point of departure for a book which transports readers from the banlieues of Paris to the banks of the Senegal River and the villages of the Anti-Atlas. In intimate ethnographic detail, the author brings to life the experiences of these older labour migrants by sharing in the life of the hostels as a resident, by observing at close quarters the men's family life on the other side of the Mediterranean as a guest in their homes, and even by accompanying them in their travels by bus, sea, and air. The monograph evaluates several theories of migration against rich qualitative data gathered from multiple methods: biographical narrative and semi-structured interviews, participant observation, and archival research. In the process, it offers a thoughtful contribution to broader debates on what it means for migrants to belong and achieve inclusion in society. "This book makes an important contribution to our understanding of transnationalism and integration. It also offers an unusually nuanced view of the strains that migration places on families" Christina Boswell, University of Edinburgh "A fascinating read which poignantly shows that the ageing-migration nexus is a theoretically profuse source of information about return migration, retirement and the meaning of home "Based on a prize-winning PhD thesis, and enriched by unique field research in migrant-worker hostels in France, this book engages in truly innovative fashion with the linked themes of migration, ageing and 'home'. " Russell King, University of Sussex .